O MARKETING ORIENTADO PELO MERCADO - Deretti, Sandro (2005)
The global economy determined deep changes in the companies’ strategic process, providing opportunities and threats in all segments and demanding competitive products and services. Therefore, the marketing function in the organizations takes greater importance in the development of sustainable competitive advantages. Many authors consider the market orientation as the essence of the business philosophy that leads to the success in the fight for markets because it investigates the consumer’s desires and necessities. This article analyzes the main works that contribute for construction of marketing concept and market orientation.